DESIGN THINKING: AN APPROACH TO RESEARCH AND INNOVATION IN NURSING - Nubya Rodrigues da Silva; Roberta Costa; Melissa Orlandi Honório Locks; Luciara Fabiane Sebold (Cogitare Enfermagem)
Objective: To analyze the application of design thinking to the scientific production of a Postgraduate Nursing Program.